Kontribusi Komponen Fisik Terhadap Kemampuan Bantingan Pinggang Pada Olahraga Gulat Siswa SMA Makassar Raya - Sarifuddin Arham; Suastika Nurafiati; Sukmawati Sukmawati (Gerak: Journal of Physical Education, Sports, and Health, 2021)
Wrestling contains the meaning of a fight, a fierce fight to defeat the opponent by hitting, kicking, strangling, and even biting each other. However, this understanding has changed because it has become a sport that is equipped with rules that are obeyed by its participants. Mastery of basic techniques is very important because determining overall skill and proficiency in a sport means having to be skilled at doing some basic movement techniques. So with a good mastery of basic techniques an athlete will have a greater chance of achieving an achievement. One of the basic techniques is the waist slam technique. This type of slamming technique utilizes the waist as a foundation for the slamming technique. To be able to perform basic techniques perfectly, it is influenced by the physical condition of the athlete. In sports, it has a very big influence on achievement or kickbacks, because the function of the legs is to support the body. Apart from being a support, the body also acts as an initial pusher and when the wrestler performs lifting and slamming movements. While the arm muscles in question is the ability of the arm muscles to pull and embrace the opponent so as not to be separated from mastery. The role of arm muscle strength in performing assistive slams is important because in addition it can help obtain the value of waist slams.